2020
DOI: 10.1002/cam4.3058
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 and IDH2 mutations in lung adenocarcinomas: Evidences of subclonal evolution

Abstract: Background Selective IDH1 and IDH2 inhibitors have been approved for targeted therapy of acute myeloid leukemia. Clinical trials for solid tumors with IDH1 and IDH2 (IDH1/2) mutations are ongoing. Reports of IDH1/2‐mutated non–small cell lung cancers (NSCLCs), however, are limited. Methods We evaluated IDH1/2 mutations in 1,924 NSCLC specimens (92% adenocarcinoma) using a next‐generation sequencing assay. Results Retrospective quality assessments identified false detection of IDH1 c.395G>A (p.R132H) resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
4
19
0
Order By: Relevance
“…The R149Q mutation in IDH2 is frequent in angioimmunoblastic T-cell lymphoma (27). In NSCLC, IDH1/2 mutations are rarely detected in primary tumors but it has been suggested that they could be branching drivers leading to subclonal evolution, based on the MAFs at which these mutations are detected (28). It is therefore not surprising that we found them upon treatment failure.…”
Section: Discussionmentioning
confidence: 76%
“…The R149Q mutation in IDH2 is frequent in angioimmunoblastic T-cell lymphoma (27). In NSCLC, IDH1/2 mutations are rarely detected in primary tumors but it has been suggested that they could be branching drivers leading to subclonal evolution, based on the MAFs at which these mutations are detected (28). It is therefore not surprising that we found them upon treatment failure.…”
Section: Discussionmentioning
confidence: 76%
“…Simultaneous genomic changes may impact biological behaviors, such as treatment response; thus, the investigation of co-occurring genomic alterations could help to stratify KRAS-mutant lung cancer patients into distinct subgroups with distinctive therapeutic responses [24]. While driver mutations (e.g., mutations in KRAS, EGFR, BRAF) are known to initiate tumor development in lung cancer, secondary mutations may promote subclonal evolution such as mutations in TP53 and PIK3CA, which were previously described in KRAS-, BRAF-, and EGFR-mutant lung tumors [25,26]. Scheffeler and colleagues conducted a study on 4507 NSCLC patients using a NGS panel containing 14 genes, and 53.5% of the mutant KRAS patients had at least one additional mutation, a percentage higher than ours, since KRAS concomitant mutations were observed in eight of 24 mutant samples (33.3%) [27].…”
Section: Discussionmentioning
confidence: 99%
“…This mutation is also frequent in angioimmunoblastic T-cell lymphoma (32). In NSCLC, IDH1/2 mutations are rarely detected in primary tumors but it has been suggested that they could be branching drivers leading to subclonal evolution, based on the MAFs at which these mutations are detected (33). In this way, Zhao et al described a case of an ALK-positive tumor in which an IDH1 variant was detected upon disease progression (34).…”
Section: Accepted Articlementioning
confidence: 99%